Aliran Filsafat Post-Positivisme dalam Pembelajaran IPA di Indonesia: Tantangan dalam Pencapaian Kompetensi Sikap Spiritual - Muh. Zaini Hasanul Muttaqin; Muhammad Sarjan; Joni Rokhmat; Asrorul Azizi; Mulia Rasyidi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This article aims to examine the flow of post-positivism philosophy in science learning in Indonesia as one of the challenges in achieving the competence of students' spiritual attitudes. The positivism paradigm holds that true knowledge must come or be based on experience, and that human reason is a requirement to consider whether experience is right or wrong according to the rules of logic and mathematical calculations, so that aspects of metaphysics that are not based on real experience are considered unclear and meaningless. The emergence of post-positivism is expected to provide a more meaningful understanding of scientific truth by shifting the concept of noumenon to phenomenon. The results show that: 1) The post-positivism paradigm is a school that wants to improve the weaknesses of positivism, which only relies on the ability to directly observe the object being observed, 2) In the learning process, core competencies for the attitude domain are not taught, but are integrated and developed. when learning aspects of knowledge and skills are carried out, 3) The practice of education in Indonesia, especially science learning, places spiritual attitude competence as a competence that is set aside which has an impact on the violation of spiritual values ​​by students, 4) The current condition of education in Indonesia cannot be separated from the dominant influence of post-positivism which suppresses the portion for aspects that are metaphysical, including spiritual aspects.